Fucosyltransferase 1 Mediates Angiogenesis in Rheumatoid Arthritis. Issue 8 (August 2014) - Isozaki, Takeo; Amin, Mohammad A.; Ruth, Jeffrey H.; Campbell, Phillip L.; Tsou, Pei‐Suen; Ha, Christine M.; Stinson, W. Alex; Domino, Steven E.; Koch, Alisa E.
<x xml:space="preserve">Abstract</x> Objective To determine the role of α(1, 2)‐linked fucosylation of proteins by fucosyltransferase 1 (FUT1) in rheumatoid arthritis (RA) angiogenesis. Methods Analysis of α(1, 2)‐linked fucosylated proteins in synovial tissue (ST) samples was performed by immunohistologic staining. Expression of α(1, 2)‐linked fucosylated angiogenic chemokine in synovial fluid (SF) was determined by immunoprecipitation and lectin blotting. To determine the angiogenic role of α(1, 2)‐linked fucosylated proteins in RA, we performed human dermal microvascular endothelial cell (HMVEC) chemotaxis and Matrigel assays using sham‐depleted and α(1, 2)‐linked fucosylated protein–depleted RA SF samples. To examine the production of proangiogenic chemokines by FUT1 in HMVECs, cells were transfected with FUT1 sense or antisense oligonucleotides, and enzyme‐linked immunosorbent assay was performed. We then studied mouse lung endothelial cell (EC) chemotaxis using wild‐type and FUT1 gene–deficient mouse lung ECs. Results RA ST endothelial cells showed high expression of α(1, 2)‐linked fucosylated proteins compared to normal ST. The expression of α(1, 2)‐linked fucosylated monocyte chemoattractant protein 1 (MCP‐1)/CCL2 was significantly elevated in RA SF compared with osteoarthritis SF. Depletion of α(1, 2)‐linked fucosylated proteins in RA SF induced less HMVEC migration and tube formation than occurred in sham‐depleted RA SF. We found that blocking FUT1 expression in ECs resulted in decreased MCP‐1/CCL2 and RANTES/CCL5 production. Finally, we showed that FUT1 regulates EC migration in response to vascular endothelial cell growth factor. Conclusion Our findings indicate that α(1, 2)‐linked fucosylation by FUT1 may be an important new target for angiogenic diseases such as RA.